GORI, encoding the WD40 domain protein, is required for pollen tube germination and elongation in rice. (21st January 2021) - Kim, Yu‐Jin; Kim, Myung‐Hee; Hong, Woo‐Jong; Moon, Sunok; Kim, Eui‐Jung; Silva, Jeniffer; Lee, Jinwon; Lee, Sangho; Kim, Sun Tae; Park, Soon Ki; Jung, Ki‐Hong
Summary: Successful delivery of sperm cells to the embryo sac in higher plants is mediated by pollen tube growth. The molecular mechanisms underlying pollen germination and tube growth in crop plants remain rather unclear, although these mechanisms are crucial to plant reproduction and seed formation. By screening pollen‐specific gene mutants in rice ( Oryza sativa ), we identified a T‐DNA insertional mutant of Germinating modulator of rice pollen ( GORI ) that showed a one‐to‐one segregation ratio for wild type (WT) to heterozygous. GORI encodes a seven‐WD40‐motif protein that is homologous to JINGUBANG/REN4 in Arabidopsis. GORI is specifically expressed in rice pollen, and its protein is localized in the nucleus, cytosol and plasma membrane. Furthermore, a homozygous mutant, gori‐2, created through CRISPR‐Cas9 clearly exhibited male sterility with disruption of pollen tube germination and elongation. The germinated pollen tube of gori‐2 exhibited decreased actin filaments and altered pectin distribution. Transcriptome analysis revealed that 852 pollen‐specific genes were downregulated in gori‐2 compared with the WT, and Gene Ontology enrichment analysis indicated that these genes are strongly associated with cell wall modification and clathrin coat assembly. Based on the molecular features of GORI, phenotypical observation of the gori mutant and its interaction with endocytic proteins and Rac GTPase, we propose that GORI plays key roles in forming endo‐/exocytosis complexes that could mediate pollen tube growth in rice. Significance Statement: Pollen tubes deliver sperm cells for fertilization in flowering plants, producing seeds. We found that Germinating modulator of rice pollen ( GORI ), a rice gene encoding a seven‐WD40‐domain protein, is essential for initiating pollen germination and tube elongation. Using CRISPR‐Cas9 gene editing, we created a homozygous mutant that exhibited male sterility through a pollen tube growth defect owing to altered pectin and actin distribution and imbalance between endocytosis and exocytosis.